PADANAN PARTIKEL AKHIR KALIMAT (SHUUJOSHI) SA DALAM BAHASA INDONESIA (STUDI KASUS PADA KOMIK) - Lubis, Clara Istina Sari; Aibonotika, Arza; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abctract:. Shuujoshi is a suffix in sentence that used to express a statement or expression of the speaker’s feeling such as feeling of emotion, appeal, prohibition, and so forth. Japanese has many end-of sentence particle, one of them is (suujoshi) sa. Sujoshii sa not only has a different uses in sentences, but also has more than one function. Some end-sentences particles have similar usage, so its always become a question for both Indonesian Japanese learners and Teachers. One of them is the meaning and use of sa. This study aims to find out the equivalent of final particle sentence (shuujoshi) sa in Indonesian which is contained in the comic series title on one piece. This research is a qualitative descriptive research and matching method. The data sources used are shuujoshi contained in the comic series one piece. The analysis used is to classify shuujoshi sa based on its equivalent in Indonesian. From the results of the analysis carried out there are 15 sentences containing shuujoshi sa and according to the theory that explains that shuujoshi sa. Where shuujoshi sa can be matched with particles and not in Indonesian. In the use of utterances between sentences (kantou-joshi) both greetings and greetings are often added. Kantou-joshi's speech is also often replaced by an intonation only (up). These forms can also be replaced with actual adverb, actually because, while the reasonableness means the meaning of the utterance.Key Words: Comic, Shuujoshi Sa, Equivalent Words